Preparation and control of quick and fast movements: Neurophysiological and dynamical perspectives - Kazutoshi Kudo; Masaya Hirashima; Akito Miura (Japanese Society of Physical Fitness and Sports Medicine, 2014)
Quickness of response and movement speed are required for achieving athletic success in a variety of sports, and are often lost in various movement disorders. Because cognitive processes such as anticipation, attention, and planning are required for preparation of a quick motor response, we first introduce recent neurophysiological studies that have revealed brain activities underlying the preparation for movement, with some neurophysiological applications to improve motor quickness. Moreover, recent developments in the dynamical analysis of complex movements allow us to understand precise mechanisms and principles underlying fast multi-joint and multi-limb movements. We introduce our current theories on the mathematical analysis of complex movement coordination called induced acceleration analysis. We propose that movements are subject to both instantaneous and cumulative effects, which combine to integrate the torque and acceleratory forces on multiple joints. We also discuss evidence that movement rate has important effects on the coordination patterns, acting as a control parameter that determines organization of movement patterns. These findings underscore the necessity of conducting research on the science of movement that is highly interdisciplinary, including the fields of physiology, biomechanics, neurosciences, and behavioral sciences not only for the enhancement of sports performance, but also for the facilitation of motor recovery and rehabilitation from neurological damage.